The Impact of Gadget Use Habits When Gathering on Family Social Interactions - Febriani, Bella (Mahogany Journal De Social, 2024)
Mobile phone usage has become an integral part of daily life, influencing various aspects of human interaction, including family relationships. This study examines the impact of mobile phone usage during family gatherings on social interaction quality, emotional bonding, and relationship satisfaction. A mixed-methods approach was used, incorporating descriptive and inferential statistical analyses from a sample of 200 respondents. The findings reveal a strong negative correlation (r = -0.68, p < 0.01) between mobile phone usage and family interaction quality, indicating that higher mobile engagement significantly reduces meaningful communication. Additionally, regression analysis (β = -0.65, p < 0.001) confirms that excessive device use predicts lower family connection. The study also highlights the emotional consequences of mobile distractions, with 42.5% of respondents reporting feelings of annoyance when ignored in favor of a mobile device. A significant difference in relationship satisfaction (p < 0.001) was found between high and low phone users, reinforcing the argument that excessive mobile use disrupts family harmony. This study fills an important gap in existing literature by focusing on family interactions rather than romantic or workplace relationships, offering practical implications for fostering mindful technology use within households. Future research should explore long-term consequences and intervention strategies to mitigate the negative effects of mobile phone distractions on family dynamics.